Mixed Infant Feeding Is Not Associated With Increased Risk of Decelerated Growth Among WIC-Participating Children in Southern California - Anderson, Christopher E.; Whaley, Shannon E.; Crespi, Catherine M.; Wang, May C.; Chaparro, M. Pia (Frontiers in Nutrition, 2021)
Background The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides nutrition assistance to half of infants born in the United States. The nationally representative WIC Infants and Toddler Feeding Practices Study-2 (ITFPS-2) reported a caloric deficit at 7 months among infants receiving WIC mixed feeding packages, suggesting these infants may be at risk for growth deceleration/faltering. Methods Longitudinal administrative data collected prospectively from WIC participants in Southern California between 2010 and 2019 were used (n=16,255). Infant lengths and weights were used to calculate weight-for-length (WLZ), weight-for-age (WAZ) and length-for-age (LAZ) z-scores at different time points. Growth deceleration/faltering was determined at 9, 12, 18 and 24 months by the change in z-score from the last measurement taken ≤6 months of age. Infant feeding was categorized by the food package (breastfeeding, mixed feeding, and formula feeding) infants received from WIC at 7 months. Poisson regression models were used to evaluate the association between WIC infant package at 7 months and deceleration/faltering at 9, 12, 18 and 24 months. Results The proportion of infants displaying decelerated/faltering growth was low for all infant food package groups. Receiving the WIC mixed feeding package at 7 months of age was not associated with WLZ, WAZ and LAZ deceleration/faltering growth. Conclusions Growth deceleration/faltering rates were very low among WIC participating children in Southern California, highlighting the critical role of nutrition assistance in supporting adequate growth in early childhood.